MENINGKATKAN KEMAMPUAN MINDS-ON DAN HANDS-ON SISWA MATERI BANGUN DATAR DENGAN MENGGUNAKAN METODE TALKING STICK - Musaadatul Fithriyah; Shinta Silviatun Najah; Fatimah Fatimah (Universitas Islam Lamongan, 2019)
Learning materials in two-dimentional figure in class II at MI Sunan Giri Merjosari Malang there are several problems namely students tend to be passive and the learning atmosphere is less pleasant because the teacher is more dominant using the lecture method so that the impact on student learning outcomes is less than the specified KKM 75 amounting to 60% of the 20 overall total students. One of the ways to improve the quality of student learning is to apply learning methods that later learning objectives can also be maximally achieved. Very diverse learning methods adapted to the material and objectives to be achieved include talking stick method including one of the learning methods carried out with the help of a stick and in turn will be held by students and who hold the mandatory answer questions from the teacher. Learning with the talking stick method is very suitable to be applied in elementary, because it can train students cognitive and psychomotor abilities, besides that the learning atmosphere is also fun and active students. This talking stick method is very appropriate to be used in the development of students' minds-on and hands-on. The purpose of this study was to determine the application of the talking stick method and the improvement of the minds-on and hands-on abilities of students in the Flat Build Class II MI Sunan Giri Merjosari Lamongan after using the talking stick method. Researchers conducted using a qualitative approach to the type of classroom action research (CAR). Analysis of the data used is descriptive qualitative techniques. The sequence of research activities includes 4 stages including: (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection. The results of the study obtained the results of the assessment of learning outcomes of the two-dimentional figure material both cycle I and cycle II of Minds-on ability in cycle I amounted to 82.25 compared to the value of Minds-on in cycle II amounted to 85.5 an increase of 3.25. Likewise with the Hans-On ability assessment there was also an increase between Cycle I an average value of 75.45 and a second cycle of 80.95 an increase of 5.5. Based on the results of the analysis of the research data it can be concluded that the use of the talking stick method can improve the minds-on and hands-on abilities of thematic learning in Class II theme 4 Flat Build Material and its properties in MI Sunan Giri Merjosari Malang and its implementation can run effectively and efficient.